Pd-ZnO nanocomposite material derived from ZIF-8 and preparation method, sensor and preparation method
By uniformly fixing Pd catalytic particles in ZIF-8-derived Pd-ZnO nanocomposites, and using the band characteristics of ZnO and the excitation of 365nm ultraviolet light, a high-selective hydrogen response in room temperature is achieved, solving the problem of high-temperature operation of the sensor, and improving safety and application prospects.
Patent Information
- Application Number
- CN202210645860.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-06-09
AI Technical Summary
The existing metal oxide semiconductor hydrogen sensors operate at high temperatures, which have high power consumption and fire explosion risks. At the same time, they have poor selectivity to hydrogen, making it difficult to achieve high selective response at room temperature.
Pd-ZnO nanocomposite material derived based on ZIF-8 is used to uniformly fix the Pd catalytic particles through metal-organic frame material. The energy band characteristics of ZnO and the excitation of 365nm ultraviolet light are used to achieve photoexcitation instead of thermal excitation, achieving high selective hydrogen response in room temperature.
It realizes a high selective response to hydrogen at room temperature, reduces the operating temperature of the sensor, eliminates the potential harm caused by high temperature, and improves the safety and application prospects of the sensor.
Smart Images

Figure CN115032240B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of gas detection technology, and specifically relates to a Pd-ZnO nanocomposite material derived from ZIF-8 and a preparation method, a sensor and a preparation method. The preparation method of the sensor is a method for preparing a room temperature hydrogen sensor based on photoexcitation high selectivity of Pd-ZnO derived from ZIF-8. Background Art
[0002] The widespread application of hydrogen is greatly hindered by its dangerous properties such as flammability, explosion and extremely low ignition energy. At the same time, hydrogen safety issues are usually caused by leakage in individual parts of the hydrogen energy system. Hydrogen has physical properties such as odorlessness, colorlessness and low density, so safe detection of hydrogen leakage is very necessary. As hydrogen plays an increasingly important role in the transition from traditional fossil energy to clean, safe and sustainable energy systems, it is of great significance to develop safe, stable, accurate, efficient, economical and portable hydrogen sensors.
[0003] Among many gas sensors, the sensors commonly used for hydrogen detection are mainly electrochemical, quartz crystal microbalance (QCM), thermal conductivity, optical and semiconductor types. Most sensor types have very prominent problems, which hinder their further promotion and application, such as fast aging and high cost of electrochemical sensors, high maintenance cost of optical sensors and high manufacturing cost of thermal conductivity sensors. Among them, metal oxide semiconductor sensors have broad application prospects due to their outstanding advantages such as low cost, high response, small size and long-term stability. At present, one of the biggest problems encountered by metal oxide semiconductor sensors in the application process is their high operating temperature. The operating temperatures of typical materials such as ZnO, SnO2 and In2O3 are all between 300 and 500 °C, which not only makes the sensor have high power consumption, but also introduces high temperature hazards in the process of detecting combustible gases such as hydrogen, increasing the risk of fire and explosion, thereby hindering the application and promotion of such sensors. At the same time, traditional metal oxide semiconductor materials also have the problem of poor selectivity for hydrogen. With the rapid development and application of hydrogen energy, facing the ever-increasing detection application scenarios and hydrogen leak detection needs, the research and development of intrinsically safe sensors with high selectivity for hydrogen at room temperature has important value and significance.
[0004] In recent years, studies have shown that ZnO-based sensors can be excited by 365nm ultraviolet light due to their 3.2eV energy band width at room temperature, thereby achieving a certain room temperature surface catalytic reaction. Previous research on ultraviolet-excited room temperature detectors was mainly aimed at the detection of special gases such as NO2, and there were few studies on combustible gases, especially hydrogen light-excited room temperature detection. At the same time, some researchers pointed out that the catalytic reaction of combustible gases on the surface of metal oxides can be promoted by doping with precious metals such as Pd, Au and Ag, but how to make the catalytic metal more evenly dispersed on the sensor surface so that the sensor has higher stability is still a technical problem that needs to be solved urgently. Summary of the invention
[0005] In order to solve the above problems, the present invention is based on the demand for new technology research and development, combined with experiments and real application scenarios, and proposes a Pd-ZnO nanocomposite material derived from ZIF-8 and a preparation method, a sensor and a preparation method. The preparation method of the sensor is a method for preparing a light-excited high-selectivity room-temperature hydrogen sensor based on ZIF-8-derived Pd-ZnO, which aims to uniformly fix the Pd catalytic particles with metal-organic framework materials, and then obtain a metal oxide semiconductor gas-sensitive material based on ZIF-8-derived Pd-ZnO through carbonization and sintering processes, and then use the energy band characteristics of ZnO and the excitation effect of 365nm ultraviolet light to replace thermal excitation with light excitation to achieve a high selective response to hydrogen at room temperature, providing a feasible new method for the design of intrinsically safe room-temperature hydrogen sensors.
[0006] The present invention firstly proposes a Pd-ZnO nanocomposite material derived from ZIF-8, wherein the material maintains a regular microscopic morphology, wherein Pd is distributed on the surface of ZnO nanoclusters to form a heterogeneous structure.
[0007] The present invention adopts the following technical solution:
[0008] A Pd-ZnO nanocomposite material derived from ZIF-8, wherein Pd is distributed on the surface of ZnO nanoclusters to form a heterogeneous structure.
[0009] The present invention provides a method for preparing the above-mentioned Pd-ZnO nanocomposite material derived from ZIF-8, comprising the following steps:
[0010] Step 1: Dissolve a zinc source, 2-methylimidazole, and a palladium source stabilized by polyvinylpyrrolidone (PVP) in methanol to form a uniform mixed solution;
[0011] Step 2: Evenly mix the 2-methylimidazole methanol solution and the PVP-stabilized palladium source methanol solution, then pour the mixture into the zinc source methanol solution, stir evenly and let stand to obtain a solid product;
[0012] Step 3: After centrifugation and washing, the obtained solid product is dried to obtain a Pd-doped ZIF-8 porous material;
[0013] Step 4: The Pd-doped ZIF-8 porous material is carbonized and sintered to obtain a ZIF-8 derived Pd-ZnO nanocomposite material.
[0014] Furthermore, in step 1, the amount of methanol used when preparing the methanol solution is 30 to 50 mL.
[0015] Furthermore, in step 1, the zinc source is Zn(NO3)2·6H2O, the palladium source is PdCl2, and the stabilizer PVP uses a molecular weight of K-30.
[0016] Furthermore, in step 1, the molar ratio of Zn(NO3)2·6H2O to 2-methylimidazole is controlled at 1:5, that is, the amount of Zn(NO3)2·6H2O is 1.4875 g, and the amount of 2-methylimidazole is 1.6422 g. The ratio of stabilizer PVP to PdCl2 is controlled at a molar ratio of 9:1.
[0017] Further, the molar ratio of PdCl2 to Zn(NO3)2·6H2O is controlled at 0.05 to 0.10: 1. For example, the molar ratio of PdCl2 to Zn(NO3)2·6H2O is controlled at 0.06:1, 0.07:1, 0.08:1, 0.09:1 or 0.10:1.
[0018] Furthermore, in step 2, the solution is stirred for 20 to 40 minutes after mixing, and the mixed solution is allowed to stand for 20 to 24 hours after stirring.
[0019] Furthermore, step 2 is specifically as follows: slowly pour the PVP-stabilized PdCl2 methanol solution into the 2-methylimidazole methanol solution, keep stirring for 20 to 40 minutes, and after stirring evenly, quickly transfer the mixed solution to 40 mL of Zn(NO3)2·6H2O methanol solution, keep stirring for 20 to 40 minutes, and let it stand for 20 to 24 hours to obtain a solid precipitate product.
[0020] Furthermore, in step 3, the solid precipitation product is placed in a vacuum oven at 50 to 80° C. and dried for 12 to 16 hours to obtain a dried Pd-doped ZIF-8 porous material.
[0021] Furthermore, in step 4, the carbonization and sintering of the Pd-doped ZIF-8 porous material includes: placing the Pd-doped ZIF-8 porous material into a tubular furnace, slowly heating it to 650°C at a heating rate of 1 to 3°C / min under an Ar atmosphere and maintaining it for 3 to 5 hours, and naturally cooling it to room temperature, so that the material completes the carbonization process and maintains the original porous morphology; placing the carbonized material in an air atmosphere, heating it to 350°C at a heating rate of 2 to 4°C / min and sintering it for 3 to 5 hours, and oxidizing the carbonized material to obtain a ZIF-8-derived Pd-ZnO nanocomposite material.
[0022] The present invention provides a light-excited high-selectivity room-temperature hydrogen sensor based on ZIF-8-derived Pd-ZnO, which uses the ZIF-8-derived Pd-ZnO nanocomposite material as described above or the ZIF-8-derived Pd-ZnO nanocomposite material prepared by the method described above, and uses a gold interdigital electrode as a sensitive electrode. The ZIF-8-derived Pd-ZnO nanocomposite material is evenly dripped on the gold interdigital electrode, and the corresponding light source above the sensor is 365nm ultraviolet light, and the irradiation intensity on the sensor surface is 2.5-10mW / cm 2 .
[0023] The present invention also provides a method for preparing the above-mentioned light-excited high-selectivity room-temperature hydrogen sensor, comprising the following steps:
[0024] Step 1: Mix the ZIF-8 derived Pd-ZnO nanocomposite with pinene alcohol and disperse them uniformly by ultrasonication, drip the dispersed solution onto the gold interdigital electrode, and place it in an oven at 60-80° C. to dry;
[0025] Step 2: Place the dried gold interdigital electrode with the nanocomposite material into a muffle furnace, heat to 350-400° C. at a heating rate of 2-5° C. / min in an air atmosphere, sinter for 3-5 hours, and then cool naturally to room temperature;
[0026] Step 3: scrape off the excess material at both ends of the sintered gold interdigital electrodes, place them in an air environment at 300-350° C. for aging for 5-7 days to obtain a hydrogen sensor based on the ZIF-8 derived Pd-ZnO nanocomposite material;
[0027] Step 4: Place the above hydrogen sensor under a 365nm ultraviolet light source, and control the light irradiation intensity on the sensor surface by adjusting the distance from the light source to the sensor surface to achieve a highly selective room temperature response to hydrogen under light excitation.
[0028] Preferably, in step 1, the mass of the ZIF-8 derived Pd-ZnO nanocomposite material is 20-40 mg; the amount of terpineol is 0.5-1.0 mL; and the volume of the nanocomposite dispersed solution dripped on the gold interdigital electrode by a pipette is 20-30 μL.
[0029] The present invention utilizes the pore characteristics of ZIF-8 and the stabilizing effect of PVP, and fixes the required content of Pd in the pores and surface of ZIF-8 by regulating the content and addition order of Zn(NO3)2·6H2O, 2-methylimidazole and PVP / PdCl2, and prepares the Pd-ZnO material with a porous microstructure through a carbonization sintering process. The Pd-ZnO nanocomposite material is prepared into a sensor by utilizing the electrical excitation and activation characteristics of ultraviolet light, and then exposed to 365nm ultraviolet light to achieve highly selective room temperature detection of hydrogen.
[0030] The advantages of the present invention compared with the prior art are:
[0031] The present invention utilizes the porous characteristics of metal-organic framework materials, uniformly fixes the Pd catalytic element, and obtains a Pd-ZnO metal oxide semiconductor gas-sensitive material derived from ZIF-8 through carbonization and sintering processes. The material has the advantages of forming a heterogeneous structure of Pd and ZnO, uniform distribution of the catalytic element Pd, and a large specific surface area. The catalytic metal Pd doping is used to improve the specific response to hydrogen, and the energy band characteristics of ZnO are combined with the excitation effect of 365nm ultraviolet light, and optical excitation is used instead of thermal excitation to achieve a highly selective response to hydrogen at room temperature, providing a feasible method for the design of intrinsically safe room temperature hydrogen sensors. Specifically:
[0032] (1) The material synthesis method is simple, the preparation process is clear, and the repeatability is strong. The overall preparation process of gas-sensitive materials has the advantages of being simple and flexible;
[0033] (2) ZIF-8 is used as the substrate material for synthesis. Since the particle size of Pd is similar to the pore size of ZIF-8, the pore structure of ZIF-8 can be fully utilized to evenly disperse Pd in the material, so that after the subsequent carbonization and sintering processes, a ZIF-8-derived Pd-ZnO metal oxide semiconductor gas-sensitive material with evenly distributed Pd can be obtained;
[0034] (3) Due to the uniform doping of catalytic metal Pd, the response performance of the prepared sensor to hydrogen is greatly improved. The Pd / ZnO heterojunction and Pd microclusters formed at room temperature make the sensor exhibit a unique p-type semiconductor response to hydrogen under 365nm ultraviolet light, while the response to other interfering combustible gases is a typical n-type semiconductor response, which achieves a unique selectivity for hydrogen at room temperature;
[0035] (4) By utilizing the energy band characteristics of ZnO and combining the electrical excitation and activation characteristics of 365nm ultraviolet light, the operating temperature of the sensor, which originally needed to be heated to 300-500°C to complete the response, was reduced to room temperature to produce a stable response. Photoexcitation replaced thermal excitation, achieving a highly selective response to hydrogen at room temperature, eliminating the potential hazards caused by the sensor's own high temperature, meeting the requirements of intrinsically safe sensors, broadening the potential application scenarios of metal oxide semiconductor sensors, and providing a reference for the further design and promotion of new semiconductor hydrogen sensors.
[0036] The method of the present invention has the advantages of a simple sensor preparation process and a highly selective response to low-concentration hydrogen at room temperature. It has broad prospects in the future in view of the huge demand for multi-scenario applications of intrinsically safe hydrogen sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0038] Figure 1 This is a scanning electron microscope (SEM) image of the Pd-doped ZIF-8 porous material prepared in Example 2 of the present invention.
[0039] Figure 2 This is a transmission electron microscope (TEM) image of the Pd-doped ZIF-8 porous material prepared in Example 2 of the present invention.
[0040] Figure 3 This is a scanning electron microscope (SEM) image of the Pd-ZnO nanocomposite porous material derived from the carbonization and sintering of Pd-doped ZIF-8 prepared in Example 2 of the present invention.
[0041] Figure 4 XRD data diagram of pure phase ZIF-8, pure phase ZnO and Pd-ZnO prepared in Examples 1 and 2 of the present invention.
[0042] Figure 5 Dynamic response-recovery curve diagram of the hydrogen sensor prepared based on ZIF-8 derived Pd-ZnO nanocomposite material prepared in Example 2 and Example 5 of the present invention to 200 ppm hydrogen at room temperature (25° C.) in dark conditions and under 365 nm ultraviolet light.
[0043] Figure 6This is a comparison chart of the dynamic response-recovery curves of the hydrogen sensor prepared based on the ZIF-8 derived Pd-ZnO nanocomposite material prepared in Examples 1, 2 and 5 of the present invention to 200 ppm hydrogen at room temperature (25°C) with and without Pd doping.
[0044] Figure 7 This is a comparison chart of the dynamic response-recovery curves of the hydrogen sensor prepared based on the ZIF-8 derived Pd-ZnO nanocomposite material prepared in Example 2 and Example 5 of the present invention to 200 ppm of H2 and CO at room temperature (25°C). DETAILED DESCRIPTION
[0045] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the preferred embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0046] The present invention adopts the following equipment:
[0047] The scanning electron microscope uses the GeminiSEM 450 field emission scanning electron microscope from Zeiss of Germany, the transmission electron microscope uses the Talos F200X from FEI for shooting, the XRD experiment is completed using the Smartlab multifunctional rotating target X-ray diffractometer, and the ultraviolet light can be achieved through a xenon lamp light source plus a 365nm filter or a 365nm LED ultraviolet bead light source.
[0048] Embodiment 1:
[0049] First, weigh 1.4875g of Zn(NO3)2·6H2O and 1.6422g of 2-methylimidazole, add 40mL of methanol respectively, and stir for 30min. Quickly transfer the fully dissolved 2-methylimidazole methanol solution to 40mL of Zn(NO3)2·6H2O methanol solution, keep stirring for 40min, and let it stand for 24h to obtain a solid precipitate product.
[0050] The solid precipitate product was purified by centrifugation for 10 minutes, and then washed with methanol. The washing and centrifugation operation was repeated three times to remove impurities. The purified solid product was placed in a vacuum oven at 60° C. and dried for 12 hours to obtain a dry pure phase ZIF-8 porous material.
[0051] After the dried pure phase ZIF-8 is placed in a tube furnace, it is repeatedly vacuumed three times in an Ar atmosphere to ensure an inert gas atmosphere in the tube, and then the temperature is raised to 650°C at a heating rate of 2°C / min, kept constant for 3 hours, and then naturally cooled to room temperature. After the tube furnace is cooled, the atmosphere is switched again, and the temperature is heated to 350°C at a heating rate of 2°C / min in an air atmosphere. After oxidation sintering for 3 hours, it is naturally cooled to room temperature, thereby obtaining a ZnO porous material derived from ZIF-8 carbonization sintering.
[0052] Embodiment 2:
[0053] First, 0.0443 g of PdCl2 and 0.2778 g of PVP (K30) were weighed, 40 mL of methanol was added, and stirred at room temperature for 3 h to fully dissolve them to obtain PVP-stabilized PdCl2. 2+ Methanol solution. Then, weigh 1.4875g of Zn(NO3)2·6H2O and 1.6422g of 2-methylimidazole, add 40mL of methanol respectively, and stir for 30min to fully dissolve them. Slowly pour the PVP-stabilized PdCl2 methanol solution into the 2-methylimidazole methanol solution, keep stirring for 30min, and after stirring evenly, quickly transfer the mixed solution to 40mL of Zn(NO3)2·6H2O methanol solution, keep stirring for 40min, and let it stand for 24h to obtain a solid precipitate product.
[0054] The solid precipitate product was purified by centrifugation for 10 min, and then washed with methanol. The washing and centrifugation operation was repeated 3 times to remove impurities. The purified solid product was placed in a vacuum oven at 60°C and dried for 12 h to obtain a dry Pd-doped ZIF-8 porous material. Figure 1 shown.
[0055] After the dried Pd-doped ZIF-8 material is placed in a tube furnace, it is repeatedly vacuumed three times in an Ar atmosphere to ensure an inert gas atmosphere in the tube, and then the temperature is raised to 650°C at a heating rate of 2°C / min, kept constant for 3 hours, and then naturally cooled to room temperature. After the tube furnace is cooled, the atmosphere is switched again, and the temperature is raised to 350°C at a heating rate of 2°C / min in an air atmosphere. After oxidation sintering for 3 hours, it is naturally cooled to room temperature, thereby obtaining a Pd-ZnO nanocomposite porous material derived from the carbonization sintering of Pd-doped ZIF-8, such as Figure 3 shown.
[0056] Figure 1 This is a scanning electron microscope (SEM) image of the Pd-doped ZIF-8 porous material prepared in Example 2 of the present invention. It can be seen from the image that after Pd doping, ZIF-8 still maintains a regular dodecahedral cage-like porous structure, and many microclusters appear on the surface.
[0057] Figure 2This is a transmission electron microscope (TEM) image of the Pd-doped ZIF-8 porous material prepared in Example 2 of the present invention. From the image, it can be seen that the Pd nanoclusters are distributed inside the ZIF-8 pores, which confirms the feasibility of the method of the present invention and successfully fixes the Pd nanoclusters uniformly inside the ZIF-8.
[0058] Figure 3 This is a scanning electron microscope (SEM) image of the Pd-ZnO nanocomposite porous material derived from the carbonization and sintering of the Pd-doped ZIF-8 prepared in Example 2 of the present invention. It can be seen from the image that the sintering process proposed by the method of the present invention can prepare a porous particle structure ZIF-8 derived Pd-ZnO nanocomposite material that maintains the original microscopic morphology.
[0059] Figure 4 XRD data diagram (Smartlab multifunctional rotating target X-ray diffractometer) of pure phase ZIF-8, pure phase ZnO and Pd-ZnO prepared in Example 1 and Example 2 of the present invention. It can be seen from the figure that ZIF-8 is successfully transformed into ZnO after the carbonization sintering process. The characteristic peak at about 40° in the Pd-ZnO curve also proves the successful doping of Pd, confirming the feasibility of the method of the present invention.
[0060] Embodiment 3:
[0061] First, weigh 0.0665 g of PdCl2 and 0.4163 g of PVP (K30), add 40 mL of methanol, and stir at room temperature for 3 h to fully dissolve them to obtain PVP-stabilized PdCl2. 2+ Methanol solution. Then, weigh 1.4875g of Zn(NO3)2·6H2O and 1.6422g of 2-methylimidazole, add 40mL of methanol respectively, and stir for 30min to fully dissolve them. Slowly pour the PVP-stabilized PdCl2 methanol solution into the 2-methylimidazole methanol solution, keep stirring for 30min, and after stirring evenly, quickly transfer the mixed solution to 40mL of Zn(NO3)2·6H2O methanol solution, keep stirring for 40min, and let it stand for 24h to obtain a solid precipitate product.
[0062] The obtained solid precipitate product was purified by centrifugation for 10 minutes, and then washed with methanol. The washing and centrifugation operation was repeated three times to remove impurities. The purified solid product was placed in a vacuum oven at 60° C. and dried for 12 hours to obtain a dry Pd-doped ZIF-8 porous material.
[0063] After the dried Pd-doped ZIF-8 material was placed in a tubular furnace, it was repeatedly evacuated three times in an Ar atmosphere to ensure an inert gas atmosphere in the tube, and then the temperature was raised to 650°C at a heating rate of 2°C / min, kept constant for 3 hours, and then naturally cooled to room temperature. After the tubular furnace cooled down, the atmosphere was switched again, and the temperature was heated to 350°C at a heating rate of 2°C / min in an air atmosphere. After oxidation sintering for 3 hours, it was naturally cooled to room temperature, thereby obtaining a Pd-ZnO nanocomposite porous material derived from the carbonization sintering of Pd-doped ZIF-8.
[0064] Embodiment 4:
[0065] First, 0.0887 g of PdCl2 and 0.5556 g of PVP (K30) were weighed, 40 mL of methanol was added, and stirred at room temperature for 3 h to fully dissolve them to obtain PVP-stabilized PdCl2. 2+ Methanol solution. Then, weigh 1.4875g of Zn(NO3)2·6H2O and 1.6422g of 2-methylimidazole, add 40mL of methanol respectively, and stir for 30min to fully dissolve them. Slowly pour the PVP-stabilized PdCl2 methanol solution into the 2-methylimidazole methanol solution, keep stirring for 30min, and after stirring evenly, quickly transfer the mixed solution to 40mL of Zn(NO3)2·6H2O methanol solution, keep stirring for 40min, and let it stand for 24h to obtain a solid precipitate product.
[0066] The obtained solid precipitate product was purified by centrifugation for 10 minutes, and then washed with methanol. The washing and centrifugation operation was repeated three times to remove impurities. The purified solid product was placed in a vacuum oven at 60° C. and dried for 12 hours to obtain a dry Pd-doped ZIF-8 porous material.
[0067] After the dried Pd-doped ZIF-8 material was placed in a tubular furnace, it was repeatedly evacuated three times in an Ar atmosphere to ensure an inert gas atmosphere in the tube, and then the temperature was raised to 650°C at a heating rate of 2°C / min, kept constant for 3 hours, and then naturally cooled to room temperature. After the tubular furnace cooled down, the atmosphere was switched again, and the temperature was heated to 350°C at a heating rate of 2°C / min in an air atmosphere. After oxidation sintering for 3 hours, it was naturally cooled to room temperature, thereby obtaining a Pd-ZnO nanocomposite porous material derived from the carbonization sintering of Pd-doped ZIF-8.
[0068] Embodiment 5:
[0069] 30 mg of the ZIF-8-derived metal oxide nanomaterial prepared in Examples 1 to 4 was mixed with 1 mL of pineneol and dispersed evenly by ultrasonication for 1 h. 25 μL of the dispersed solution was dripped on the gold interdigital electrode, which was then placed in an oven at 60° C. and dried for 12 h.
[0070] The dried gold interdigitated electrode with the nanocomposite material is placed in a muffle furnace, heated to 400°C at a heating rate of 5°C / min in an air atmosphere, sintered for 4 hours, and then naturally cooled to room temperature;
[0071] After scraping off the excess covering material at both ends of the sintered gold interdigital electrodes, the electrodes were placed in an air environment and aged at 350° C. for 5 days to obtain a hydrogen sensor based on a ZIF-8 derived Pd-ZnO nanocomposite material.
[0072] The hydrogen sensor is placed under a 365nm ultraviolet light source, and the light irradiation intensity on the sensor surface is controlled by adjusting the distance from the light source to the sensor surface, thereby achieving a highly selective room temperature response to hydrogen under light excitation.
[0073] Figure 5 (a) is a dynamic response-recovery curve of the hydrogen sensor prepared based on the ZIF-8 derived Pd-ZnO nanocomposite material prepared in Examples 2 and 5 of the present invention at room temperature (25° C.) in the dark to 200 ppm hydrogen, Figure 5 (b) is a dynamic response-recovery curve of the hydrogen sensor prepared based on the ZIF-8 derived Pd-ZnO nanocomposite material prepared in Examples 2 and 5 of the present invention to 200 ppm hydrogen at room temperature (25° C.) under 365 nm ultraviolet light, Figure 5 (a) with Figure 5 From the comparison of (b), it can be seen that the light excitation experimental method proposed in the present invention has significantly improved the sensor based on ZIF-8 derived Pd-ZnO nanomaterials without a heating source. Figure 5 (a) shows that under dark conditions, since the carriers inside the material are not activated at room temperature, there is a large signal fluctuation noise, and there is no obvious response to hydrogen. Figure 5 It can be seen from (b) that when the ZIF-8 derived Pd-ZnO nanomaterial sensor is placed under the excitation of 365nm ultraviolet light, due to the energy band characteristics of ZnO and the excitation of ultraviolet light, not only the signal noise of the base resistor is eliminated at room temperature, and the room temperature rectification effect is achieved, but also due to the formed Pd / ZnO heterojunction and Pd microclusters, the sensor exhibits an obvious and unique p-type semiconductor response to low concentrations of hydrogen under 365nm ultraviolet light, which proves the feasibility of the intrinsically safe hydrogen sensor proposed by the method of the present invention using light excitation instead of thermal excitation.
[0074] Figure 6The following is a comparison of the dynamic response-recovery curves of hydrogen sensors prepared based on ZIF-8 derived Pd-ZnO nanocomposites prepared in Examples 1, 2 and 5 of the present invention at room temperature (25°C) for 200ppm hydrogen with and without Pd doping. As can be seen from the figure, for pure phase ZIF-8 derived ZnO, 365nm ultraviolet light excitation can only realize its own response characteristics as a typical n-type semiconductor material, while after doping with 5.0% molar ratio of Pd, the sensor realizes a unique p-type response to hydrogen under 365nm ultraviolet light, and its response / recovery time is shorter, which shows that the ZIF-8 derived Pd-ZnO nanocomposites proposed by the method of the present invention have unique advantages for room temperature light-excited hydrogen detection.
[0075] Figure 7 The following is a comparison of the dynamic response-recovery curves of the hydrogen sensor prepared based on the ZIF-8 derived Pd-ZnO nanocomposite prepared in Example 2 and Example 5 of the present invention to 200ppm H2 and CO at room temperature (25°C). In the process of hydrogen detection by typical metal oxide semiconductor sensors in the past, common combustible gases such as CO usually have the same dynamic response trend as H2, that is, they all show the response trend of n-type or p-type semiconductors, while Figure 7 It can be found that at room temperature, the ZIF-8-derived Pd-ZnO photoexcitation sensor proposed by the method of the present invention can achieve a p-type semiconductor response unique to hydrogen, which achieves a highly selective response to hydrogen at room temperature. In places where single detection of hydrogen is required, the method proposed by the present invention has great application prospects.
[0076] Parts of the present invention that are not described in detail belong to the well-known technology in the art.
[0077] Although the above describes the illustrative specific embodiments of the present invention to facilitate those skilled in the art to understand the present invention, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
Claims
1. A light-excited room temperature hydrogen sensor based on ZIF-8 derived Pd-ZnO, using a ZIF-8 derived Pd-ZnO nanocomposite material, characterized in that: Pd is distributed on the surface of ZnO nanoclusters to form a heterogeneous structure; the Pd-ZnO nanocomposite material derived from ZIF-8 is prepared by the following method, which includes the following steps: Step 1: Dissolve a zinc source, 2-methylimidazole and a palladium source stabilized with PVP in methanol to form a uniform mixed solution; the zinc source is Zn(NO3)2·6H2O, and the palladium source is PdCl2; the molar ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:4-6; the molar ratio of PVP to PdCl2 is 8-10:1; the molar ratio of PdCl2 to Zn(NO3)2·6H2O is 0.06-0.10:1; Step 2: After uniformly mixing the 2-methylimidazole methanol solution and the PVP-stabilized palladium source methanol solution, pouring the mixture into the zinc source methanol solution, stirring evenly and then standing to obtain a solid product; Step 3: After centrifugation and washing, the obtained solid product is dried to obtain a Pd-doped ZIF-8 porous material; Step 4: The Pd-doped ZIF-8 porous material is carbonized and sintered to obtain a ZIF-8 derived Pd-ZnO nanocomposite material.
2. The light-excited room temperature hydrogen sensor according to claim 1, characterized in that: In step 1, the amount of methanol used when preparing the methanol solution is 30-50 mL; In step 1, the molar ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:
5. The molar ratio of PVP to PdCl2 is 9:
1.
3. The light-excited room temperature hydrogen sensor according to claim 1, characterized in that: In step 2, the stirring time is 20 to 40 min, and after the stirring is completed, the mixed solution is allowed to stand for 20 to 24 h; Step 2 is specifically as follows: Pour the PVP-stabilized PdCl2 methanol solution into the 2-methylimidazole methanol solution, keep stirring for 20 to 40 minutes, and after stirring evenly, transfer the mixed solution into 40 mL of Zn(NO3)2·6H2O methanol solution, keep stirring for 20 to 40 minutes, and let it stand for 20 to 24 hours to obtain a solid precipitate product.
4. The light-excited room temperature hydrogen sensor according to claim 1, characterized in that: In step 3, the solid product is placed in a vacuum oven at 50-80° C. and dried for 12-16 h to obtain a dried Pd-doped ZIF-8 porous material.
5. The light-excited room temperature hydrogen sensor according to claim 2, characterized in that: In step 4, the carbonization and sintering of the Pd-doped ZIF-8 porous material includes: placing the Pd-doped ZIF-8 porous material into a tubular furnace, heating it to 650°C at a heating rate of 1~3°C / min under an Ar atmosphere and maintaining it for 3~5 hours, and naturally cooling it to room temperature to complete the carbonization process of the material and maintain the original porous morphology; placing the carbonized material in an air atmosphere, heating it to 350°C at a heating rate of 2~4°C / min and sintering it for 3~5 hours, and oxidizing the carbonized material to obtain a ZIF-8-derived Pd-ZnO nanocomposite material.
6. The light-excited room temperature hydrogen sensor according to claim 1, characterized in that: The gold interdigital electrode is used as the sensitive electrode. The Pd-ZnO nanocomposite material derived from ZIF-8 is evenly dripped on the gold interdigital electrode. The corresponding light source above the sensor is 365nm ultraviolet light, and the irradiation intensity on the sensor surface is 2.5~10 mW / cm 2 .
7. A method for preparing the light-excited room temperature hydrogen sensor as claimed in claim 6, characterized in that: The steps include: Step 1: Mix the ZIF-8-derived Pd-ZnO nanocomposite with pinene alcohol and disperse them uniformly by ultrasonication, drip the dispersed solution onto the gold interdigital electrode, and place it in an oven at 60-80°C to dry; Step 2: Place the dried gold interdigital electrode with the nanocomposite material in a muffle furnace, heat to 350-400°C at a heating rate of 2-5°C / min in an air atmosphere, sinter for 3-5 hours, and then cool naturally to room temperature; Step 3: scrape off the excess material at both ends of the sintered gold interdigital electrodes, place them in an air environment at 300-350 °C for aging for 5-7 days, and obtain a hydrogen sensor based on the ZIF-8 derived Pd-ZnO nanocomposite material; Step 4: Place the above hydrogen sensor under a 365 nm ultraviolet light source, and control the light irradiation intensity on the sensor surface by adjusting the distance from the light source to the sensor surface to achieve selective room temperature response to hydrogen under light excitation.
8. The method according to claim 7, characterized in that: In step 1, the mass of the ZIF-8 derived Pd-ZnO nanocomposite material is 20-40 mg; the amount of pineneol is 0.5-1.0 mL; and the volume of the nanocomposite dispersion solution dripped on the gold interdigital electrode by a pipette is 20-30 μL.
Citation Information
Patent Citations
Gas sensor and member using metal oxide nanotubes including nanoscale heterogeneous catalysts by using metal-organic framework, and manufacturing method thereof
KR1020180065493A